1980
DOI: 10.1038/ki.1980.42
|View full text |Cite
|
Sign up to set email alerts
|

Total body electrolyte composition and distribution of body water in uremia

Abstract: Total body sodium and chloride were measured by neutron activation analysis, and total body potassium was measured by whole body counting in ten male patients with endstage renal disease requiring chronic maintenance hemodialysis. The extracellular fluid volume was estimated from the simultaneously measured volume of distribution of bromine 77 and sodium 24. Total body water was estimated from the volume of distribution of triated water. Total body sodium and chloride were significantly increased above normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 16 publications
2
17
0
2
Order By: Relevance
“…In uraemic subjects, however, it is pertinent to consider critically the accuracy of ICW estimated as TBW minus corrected sodium bromide space. Although the latter is the preferred method of ECV estimation in normal subjects (1 l), its measurement is relatively imprecise, and abnormal cell membrane permeability to small molecules in uraemia (28) might lead to an overestimate of ECV by bromide and a corresponding underestimate of ICW; however, studies of electrolyte distribution in uraemic adults by Brennan et al (6) suggest that the increased bromide space reflects a genuine increase in ECV. These investigators have also shown a close correlation in uraemic subjects between ICW calculated from TBW minus corrected sodium bromide space and TBK similar to that previously described in normals (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In uraemic subjects, however, it is pertinent to consider critically the accuracy of ICW estimated as TBW minus corrected sodium bromide space. Although the latter is the preferred method of ECV estimation in normal subjects (1 l), its measurement is relatively imprecise, and abnormal cell membrane permeability to small molecules in uraemia (28) might lead to an overestimate of ECV by bromide and a corresponding underestimate of ICW; however, studies of electrolyte distribution in uraemic adults by Brennan et al (6) suggest that the increased bromide space reflects a genuine increase in ECV. These investigators have also shown a close correlation in uraemic subjects between ICW calculated from TBW minus corrected sodium bromide space and TBK similar to that previously described in normals (36).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular water includes reduction in alkaline soluble protein on muscle biopsy (ICW), an index of body cell mass, was reduced compared to (17), decreased whole body protein and albumin turnover (4, 16), values predicted for height in 14 children studied under years of decreased plasma and intracellular concentrations of certain esage lGroup I, mean ICW observed:predicted ratio (O/P) 0.67, sential amino acids (7,27), decreased levels of short half-life serum range 0.50-0.931, but was normal in seven prepubertal children proteins (27,47), an increased protein catabolic response to fasting studied between 5-1 1.9 years of age ( G~~~~ 11, mean ICW O/P (221, reduced total body nitrogen (341, and reduced body cell mass 1.01, range 0.88-1.23, P < 0.01 compared to Group I). Both ICW as estimated by measurement of ICW (6,14,15,19) and total O/P and weight for height index increased significantly with age body potassium (TBK) (39, 43). In infancy, when calorie and throughout childhood ( r = 0.79, P < 0.001 and r = 0.62, P < 0.05, protein requirements per kg and rates of growth and nitrogen respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the well-known age-related decline in FFM, TBW and ICW reduced in elderly persons [19]. In addition, ICW has been observed to reduce in clinical situations in which TBW is increased, such as uremia, post-trauma, or cirrhosis [20].…”
Section: Intracellular Water/total Body Watermentioning
confidence: 99%
“…Entretanto, a avaliação da CC de pacientes com IRC é dificultada por alterações hidroeletrolíticas e perda de massa óssea por osteodistrofia renal, frequentes nessa população 33,34 .…”
Section: Avaliação Da Composição Corporal Na Insuficiência Renal Crônunclassified